2014
DOI: 10.1111/ejh.12202
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin inhibitor rapamycin enhances anti‐leukemia effect of imatinib on Ph+ acute lymphoblastic leukemia cells

Abstract: BCR-ABL fusion gene typically causes a type of acute lymphoblastic leukemia (ALL), known as Ph+ ALL. Although imatinib (IM) treatment induced high rates of complete response (CR), serious acute and late complications are frequent, whereas more vexatiously resistance to chemotherapy and clinical relapse develops. Therefore, the efficacy of treatment in Ph+ ALL is still to be determined. In this study, we focused our attention on the potential benefit of rapamycin (RAPA), an mammalian target of rapamycin (mTOR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Cytofluorometric analysis of the apoptotic cell fraction was performed by measuring the uptake of Annexin V (KeyGEN biotech, Nanjing, China) and PI (Sigma-Aldrich Corporation, USA) according to the published protocol [27]. …”
Section: Methodsmentioning
confidence: 99%
“…Cytofluorometric analysis of the apoptotic cell fraction was performed by measuring the uptake of Annexin V (KeyGEN biotech, Nanjing, China) and PI (Sigma-Aldrich Corporation, USA) according to the published protocol [27]. …”
Section: Methodsmentioning
confidence: 99%
“…Yang et al . showed that combining imatinib therapy with rapamycin overcame this effect and enabled induction of autophagy and cell cycle arrest in primary Ph+ B-ALL cells in vitro [138]. …”
Section: Mtor and B Cell Neoplasmsmentioning
confidence: 99%
“…Deletion of PI3K inhibited leukemogenesis in a murine model of p190 Ph + ALL. A dual PI3K/MTOR inhibitor was effective on Ph + ALL patient samples (53) and showed synergy with Imatinib (54). The activation of AKT and MTOR signaling also plays a critical role in steroid resistance in ALL (55, 56), and multiple agents targeting the PI3K/AKT/MTOR axis are currently in clinical trials for pediatric ALL [reviewed in Ref.…”
Section: The Biology Of Philadelphia Chromosome-positive Allmentioning
confidence: 99%